The Capture of EU Football Regulation by the Football Governing Bodies - Henk Erik Meier; Borja García; Serhat Yilmaz; Webster Chakawata (JCMS: Journal of Common Market Studies, 2022)
The article traces how European football regulation has been `captured' by the football governing bodies. The European Commission re-aligned with the European football governing body Union des Associations Européennes de Football (UEFA), which enabled the latter to solidify its role as industry regulator. Four factors seem to account for the successful capture of European football regulation by UEFA. (1) UEFA enjoys a substantial mobilization advantage. (2) As legitimacy maximizer, the Commission avoids unnecessary confrontations. (3) Substantial interest heterogeneity amongst football stakeholders such as clubs, players and leagues prevented the emergence of strong countervailing constituencies to oppose UEFA regulatory proposals. (4) The legacy of amateur ideology in European football nurtures a strong socio-cultural regulatory frame, which depicts the football governing bodies as trustees of the public interest in football as community institution. The findings come with implications for EU football regulation and the limits of the EU regulatory state.
Keywords: 330; UEFA; football regulation; reputation; lobbying; regulatory bodies; regulatory capture